Susceptibility of Tsetse Species to Glossina pallidipes Salivary Gland Hypertrophy Virus (GpSGHV) - Demirbas-Uzel, Güler; Kariithi, Henry M.; Parker, Andrew G.; Vreysen, Marc J. B.; Mach, Robert L.; Abd-Alla, Adly M. M. (Frontiers in Microbiology, 2018)
Salivary gland hytrosaviruses (SGHVs, family Hytrosaviridae) are non-occluded dsDNA viruses that are pathogenic to some dipterans. SGHVs primarily replicate in salivary glands (SG), thereby inducing overt salivary gland hypertrophy (SGH) symptoms in their adult hosts. SGHV infection of non-SG tissues results in distinct pathobiologies, including reproductive dysfunctions in tsetse fly, Glossina pallidipes (Diptera: Glossinidae) and house fly. Infection with the G. pallidipes virus (GpSGHV) resulted in the collapse of several laboratory colonies, which hindered the implementation of area wide integrated pest management (AW-IPM) programs that had a sterile insect technique (SIT) component. Although the impact of GpSGHV infection has been studied in some detail in G. pallidipes, the impact of the virus infection on other tsetse species remains largely unknown. In the current study, we assessed the susceptibility of six Glossina species (G. pallidipes, G. brevipalpis, G. m. morsitans, G. m. centralis, G. f. fuscipes and G. p. gambiensis) to GpSGHV infections, and the impact of the viral infection on the fly pupation rate, adult emergence, and virus replication and transmission from the larval to adult stages. We also evaluated the ability of the virus to infect conspecific Glossina species through serial passages. The results indicate that the susceptibility of Glossina to GpSGHV varied widely amongst the tested species, with G. pallidipes and G. brevipalpis being the most susceptible and most refractory to the virus, respectively. Further, virus injection into the hemocoel of teneral flies led to increased viral copy number over time, while virus injection into the third instar larvae delayed adult eclosion. Except in G. pallidipes, virus injection either into the larvae or teneral adults did not induce any detectable SGH symptoms, although virus infections were PCR-detectable in the fly carcasses. Taken together, our results indicate that although GpSGHV may only cause minor damage in the mass-rearing of tsetse species other than G. pallidipes, preventive control measures are required to avoid viral contamination and transmission in the fly colonies, particularly in the facilities where multiple tsetse species are reared.